Solo Dining at Home in the Company of ICT Devices - Nicolau i Torra, Núria; Lemke, Mailin; Huisman, Gijs (Frontiers in Computer Science, 2022)
The consumption of a solo meal is often subject to negative associations. Studies indicate that solo diners use information and communication technology (ICT) devices such as smartphones, to mitigate negative experiences such as boredom and loneliness, especially when dining in a public context. However, we know less about the motivation to use such devices and consequent meal experiences in a private context. For this exploratory qualitative study, we asked participants to fill out a cultural probes kit to capture their dining experience and use of ICT devices over a period of five days. Once completed, the content was discussed with participants during a semi-structured interview. Data was analysed using thematic analysis in a deductive and inductive form leading to four themes: (1) The experience of eating with others; (2) The use of electronic devices while eating; (3) The meaning of food; and (4) Relaxing features and influences. Participants indicated that eating alone can be a pleasurable experience that people enjoy and perceive as relaxing. ICT devices were named to play an essential part in the dining experience. The entertainment that devices provide can mitigate feelings of loneliness and uncomfortable silence when eating by oneself. We reflect on the findings and point out potential design avenues for future studies.